Changes of the level of galectin-3, β-2-microglobulin, albuminuria and end glycation products in patients with chronic heart failure and atrial fibrillation under the influence of treatment. - Kuryata, O. V.; Muhammad, Muhammad; Mytrokhina, S. S. (Medicni Perspektivi, 2018)
The combination of chronic heart failure and atrial fibrillation is considered one of the most prognostically unfavorable alliances among cardiovascular diseases. Now the need for new markers as potential targets for therapeutic intervention is being actively discussed. To date, active study of cardiorenal syndrome continues, which in turn leads to an active search for drugs that reduce nephrologic risk, especially in the category of people with a combined cardiovascular pathology. The aim of the study was to compare the effects of irbesartan and ACE inhibitors on the level of galectin-3, β-2-microglobulin, albuminuria and end glycation products (AGE) in patients with chronic heart failure with atrial fibrillation and impaired renal function. The results of the effect of drugs in patients with chronic heart failure and atrial fibrillation are presented and analyzed. The data indicate the need for more careful attention to this group of patients, namely, the need to diagnose the functional of the kidneys, which is very important for the development of effective interventions aimed at preventing the progression of these diseases.